2021
DOI: 10.3390/cryst11091075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and Type of Stirring on the Spontaneous Precipitation of CaCO3 at Identical Initial Supersaturation, Ionic Strength and a(Ca2+)/a(CO32−) Ratio

Abstract: CaCO3 precipitation is physical-chemical basis of biomineral formation of hard tissue (shells, skeletons) in marine calcifying organisms (=biomineralization). Processes controlling biomineralization are still not fully clarified, so the study of influence of pH on basic processes of CaCO3 precipitation should contribute to better understanding of biomineralization under climate change. This paper reports on the effect of initial pH (pH0) and type of stirring (mechanical and magnetical) on spontaneous precipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…88,120–122 To this aim, Trofimov et al 95 suggested that an increase in pH from 7 to 11 may lead to the precipitation of vaterite, which was explained by the observations of alterable supersaturation and increased CO 3 2− content, but that the addition of negatively-charged inorganic or organic substances appeared to have the same effect. Moreover, Džakula et al 122 showed that in systems in which the supersaturation, ionic strength, ratio of the activity of the constituent ions ( a (Ca 2+ )/ a (CO 3 2− )), and the type of stirring were identical that the calcite content increased with an increase in the pH from 8.5 to 10.5, while in the same systems that were magnetically stirred with the pH controlled at 8.5 and 9.0, the precipitated product was almost entirely vaterite. The morphology of the resultant vaterite was observed to continuously change with increasing pH.…”
Section: Controlled Synthesis Of Caco3 Mnps and Formation Mechanismsmentioning
confidence: 99%
“…88,120–122 To this aim, Trofimov et al 95 suggested that an increase in pH from 7 to 11 may lead to the precipitation of vaterite, which was explained by the observations of alterable supersaturation and increased CO 3 2− content, but that the addition of negatively-charged inorganic or organic substances appeared to have the same effect. Moreover, Džakula et al 122 showed that in systems in which the supersaturation, ionic strength, ratio of the activity of the constituent ions ( a (Ca 2+ )/ a (CO 3 2− )), and the type of stirring were identical that the calcite content increased with an increase in the pH from 8.5 to 10.5, while in the same systems that were magnetically stirred with the pH controlled at 8.5 and 9.0, the precipitated product was almost entirely vaterite. The morphology of the resultant vaterite was observed to continuously change with increasing pH.…”
Section: Controlled Synthesis Of Caco3 Mnps and Formation Mechanismsmentioning
confidence: 99%
“…44 The ratio of bicarbonate/carbonate can decrease as the soil pH becomes alkaline, which can cause higher nucleation rates and faster precipitation of CaCO 3 crystals with smaller size. 44,45 If there are sufficient CO 2 , CO 3 2−…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Kontrec et al [1] in their paper indicate a significant contribution of initial pH to the overall effect of all parameters relevant to precipitation processes and biomineralization. This paper reports on the influence of initial pH and type of stirring on the kinetics, phase composition, size, and morphology of spontaneously precipitated calcium carbonate (CaCO 3 ).…”
mentioning
confidence: 94%